Fertilizer transportation problem using Vogel Approximation method - R.H., Kankarofi; U.A., Yakubu; I. M., Sulaiman; M., Mamat; Sukono, .; M.P.A., Saputra (2021)
This research work was designed to optimize the processes of transporting fertilizer from Kano State Agricultural Supply Company, KASCO, Maiduguri Road, Kano, also implement the distribution route that lead to the reduction of operating cost of transportation problems that usually occurs due to the nature of bad roads to some selected local government in Kano state Nigeria. To minimize the cost of shipping fertilizer from the company to the destinations a mathematical optimization model (Vogel Approximation method) has been used to ease the cost and the distribution of fertilizer to the various locations.